Iniltration vs. instillation of ropivacaine 7.5% in radical mastectomies for postoperative analgesia - Yolanda Prieto, Blanca Irma; Millán Corrales, Alba Lorena; Palacios Ríos, Dionicio; Garduño Chávez, Belia Inés; López Cabrera, Norma Guadalupe; Millán Cornejo, Gustavo Adolfo; González Rocha, B. T. (UANL. Facultad de Medicina, 2014)
Objective: Determining the effectiveness of iniltration versus instillation with 7.5% ropivacaine in reducing the intensity of postoperative pain in patients undergoing a radical mastectomy. Material and methods: Clinical, prospective, and comparative analytical study in a sample of 20 female patients between 20 and 60 years of age, ASA I and II, weight 50-90 kg, who were divided into 2 groups (10 patients each). In Group 1 infiltration with ropivacaine 7.5% (20 ml) was applied prior to closure of the surgical wound, meanwhile in Group 2 ropivacaine 7.5% (20 ml), was instilled into the surgical wound. P ain intensity was assessed by a visual analog scale (V AS) upon extubation. The need for rescue medication and the incidence of nausea and vomiting were measured from 0 to 30 minutes postoperatively and at 2, 4, 8 and 12 hours. Results: There was no statistical difference between the groups (only the group managed through iniltration required rescue medications), but the iniltration group had a lower perception of pain. Conclusions: This study reported the same eficacy of preventive treatment of postoperative pain in patients who underwent radical mastectomy for instillation and iniltration with 7.5% ropivacaine and little need for rescue medication postoperatively.